COMENTARIO HISTÓRICO A LA LAKEDAIMONÍON POLITEÍA DE JENOFONTE. - Fornis, César (Talia Dixit, 2025)
For ages, Xenophon's Lakedaimonion Politeia had been widely interpreted as the work in which the Athenian author, considered a laconophile--as a good Socratic--most clearly showed his enthusiasm for the laws, institutions and habits that tradition attributed to Lycurgus and which made Sparta the only place where moral excellence prevailed. The historical commentary with bibliographical update that we offer on this treatise confirms that, with certain nuances, this reading is still valid in the face of those who in recent decades, encouraged by a certain revisionism, have seen in Xenophon a critic of the Lycurgan order--for some subtle, for others ruthless--both in ideals and in practice.